Representações para atores sociais em boletins de ocorrência de crimes de injúria - Ribeiro, Marcos Rogério (2014)
Among the social practices of the judiciary police system of activities and genres, is included the police report (PR), a text that reports criminal events and, in some cases, non criminal events, being one of the most produced documents in the system of police activities. The PR serves as a starting point for many others subsequent acts in which can be required decision-making of all kinds, including judicial decision, which can influence the everyday lives of people, due to the performative feature of legal genres. Therefore, this research aims to investigate the use of language to represent social actors involved in PRs on crimes of injúria. For this purpose, we carried out an analysis of a corpus containing 40 PRs of injúria randomly selected from a universe of research of 2,795 PRs of crimes against honour recorded from 01-09-2011 to 30-09-2011, covering the entire territory of Rio Grande do Sul state, collected via download from the Civil Police integrated consultation page. The access and use of BOs for the research was approved by the state Chief of Police, ensuring the confidentiality of the identity and privacy of those involved in the events. Forty PRs were randomly chosen for analysis, five for each pair of social actors involved with higher recurrence rate in the verbal conflict as offender and offended, as following: neighbor versus neighbor, ex-husband versus ex-wife, husband versus wife, supplier versus customer, mother-in-law versus son-in-law/daughter-in-law, employer versus employee, parents versus children and father-in-law versus son-in-law/daughter-in-law. The analysis is mainly based on the Systemic Functional Linguistics (HALLIDAY, 1978), the Systemic Functional Grammar (HALLIDAY; MATTHIESSEN, 2004), the Theory of Appraisal (MARTIN; WHITE, 2005), the Theory of Social Representations (MOSCOVICI, 1961) and the modes of stigmatization proposed by Goffman (1963) and Elias and Scotson (1994). The results show that, in the analyzed texts, verbal processes play a key role in the lexical-grammatical configuration of the narrative section of PRs, by delimiting the voices assigned to the offender and the offended and introducing the offensive diction. Because of this, the relationship between projecting and projected clauses is recurring, with the prevalence of projected clauses represented as a Report, in which occur the representations for offenses. The offenders typically function as Sayer of the offensive diction and the offended as Target. Regarding the relationship between offender, offended and offense, we found in verbal clauses the pattern Sayer-Target-Verbiage, respectively. Regarding the relationship between offended and offense, we found in relational clauses the pattern Carrier-Attribute, respectively. From a semantic-discursive standpoint, the offended are represented by offenders through explicit negative attitudinal evaluations, revealing judgements of social sanction and social esteem, which in terms of social representation predominantly evoke, through the use of epithets, stigmas related to defects of individual character and anomie of sexual immorality. In the process of social representation, the use of epithets is anchored in socially constructed and shared ideologies, beliefs, conventions and stereotypes.